2013
DOI: 10.1098/rspb.2013.0502
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies coexistence of trees in tropical forests: spatial signals of topographic niche differentiation increase with environmental heterogeneity

Abstract: Neutral and niche theories give contrasting explanations for the maintenance of tropical tree species diversity. Both have some empirical support, but methods to disentangle their effects have not yet been developed. We applied a statistical measure of spatial structure to data from 14 large tropical forest plots to test a prediction of niche theory that is incompatible with neutral theory: that species in heterogeneous environments should separate out in space according to their niche preferences. We chose pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 53 publications
(86 reference statements)
4
93
0
4
Order By: Relevance
“…Environmental heterogeneity, which manifests in difference in environmental conditions among sites, can lead to niche differentiation [43], and consequently to segregated co-occurrence patterns [44]. A positive relationship between environmental heterogeneity and the prevalence of segregated co-occurrence patterns was reported before [27].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental heterogeneity, which manifests in difference in environmental conditions among sites, can lead to niche differentiation [43], and consequently to segregated co-occurrence patterns [44]. A positive relationship between environmental heterogeneity and the prevalence of segregated co-occurrence patterns was reported before [27].…”
Section: Discussionmentioning
confidence: 99%
“…,b; Brown et al. ), suggesting scale dependency in niche partitioning related to edaphic conditions. Our results also hint at an interaction between soil type and rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…,b; Brown et al. ). Furthermore, plants exhibit functional differences in response to temperature (Moles et al.…”
Section: Introductionmentioning
confidence: 99%
“…These are the same basic variables used by other studies that reported compelling effects of habitat characteristics on tree species' distributions (Harms et al 2001, Bohlman et al 2008, Bagchi et al 2011, Brown et al 2013, Ledo et al 2013. For habitat specialization, we used a set of topographical variables: elevation, slope, curvature, and aspect per 20 3 20 m quadrats throughout the plot.…”
Section: Analysesmentioning
confidence: 99%